The Role of Higher Education in the Professionalisation of Adult Educators - Gravani, Maria N.; Zarifis, George K.; Jogi, Larissa (Cambridge Scholars Publisher, 2020)
This collection of essays focuses on the important, but under-discussed, role of higher education institutions in both delivering academic programmes that provide relevant cognitive and professional skills and competences to future adult educators, and in being more actively involved in the current dialogue with regard to the professionalization paths of adult educators and trainers. The topics discussed here vary from the initial education and training of adult educators in higher education environments, to the role of universities as validating agencies of existing psycho-pedagogical competences for in-service adult educators. Particular attention is also drawn to the ways in which adult education policies and initial education and training opportunities for prospective adult educators affect the role of higher education institutions in terms of academic orientation and programme delivery.